Distributed Information Processing in Biological and Computational Systems. - NAVLAKHA, SAKET; BAR-JOSEPH, ZIV (Communications of the ACM, 2015)
The article looks at the intersection of computing and biology, focusing on the implications of the presence of distributed algorithms of control and information processing in both computational and biological systems. It notes that researchers in each discipline are making use of models from the other and discusses how the most useful topics of such intersecting studies can be identified. Topics include the network of finite state machines (nFSM)-based communication model, shared memory models, and stochastic decision-making.